Transformational shifts through digital servitization - Tronvoll, Bård; Sklyar, Alexey; Sörhammar, David; Kowalkowski, Christian (Industrial marketing management, 2020)
Manufacturers increasingly look to digitalization to drive service growth. However, success is far from guaranteed, and many firms focus too much on technology. Adopting a discovery-oriented, theories-in-use approach, this study examines the strategic organizational shifts that underpin digital servitization. Notwithstanding strong managerial and academic interest, this link between digitalization and servitization is still under-investigated. Depth interviews with senior executives and managers from a global market leader revealed that to achieve digital service-led growth, a firm and its network need to make three interconnected shifts: (1) from planning to discovery, (2) from scarcity to abundance, and (3) from hierarchy to partnership. Organizational identity, dematerialization, and collaboration play a key role in this transformation. For managers, the study identifies a comprehensive set of strategic change initiatives needed to ensure successful digital servitization. •Three strategic organizational shifts are needed for digital servitization success.•The key role of organizational identity, dematerialization, and collaboration•Digital servitization requires changes within both the firm and its entire network.•New business models centered around big data are driving competitive advantage.•Agile mindset and ways of working are imperative for digital servitization.